TINDAK PIDANA JUDI DALAM QANUN ACEH NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT - Azharuddin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2019)
Gambling is a criminal offense in positive law in Indonesia, the regulation of gambling offenses is not only found in the Criminal Code as the parent of Indonesian criminal law, but also in other regulations. Aceh, which has been given a mandate to implement Islamic sharia, has also regulated the problem of gambling in the form of a qanun (Perda), a matter raised regarding gambling rules in a qanun that limits the gambling crime by betting or a minimum profit value of 2 grams of pure gold. Gambling criminal rules contained in the qanun as if to provide opportunities for the public to make bets in each game with a value of bets and profits below 2 grams of gold, even more so in today's era of sophisticated, where gambling promotions occur in everywhere and offer low stakes and can be accessed by anyone. Therefore, the gambling regulations in the Aceh qanun should explain more about betting and the value of profits below 2 grams of pure gold, so that gambling practices in Aceh can be eliminated in the future.